Ultrasound-activated peroxydisulfate process with copper film to remove bisphenol A: Operational parameter impact and back propagation-artificial neural network modeling - Chu, Jae Hun; Kang, Jin Kyu; Park, Seong Jik; Lee, Chang Gu (Journal of Water Process Engineering, 2021)
Combining the ultrasound and peroxydisulfate (US-PDS) process, offers a promising advanced oxidation method to remove organic compounds from aqueous solutions. This study evaluated the activation of PDS by US irradiation based on bisphenol A (BPA) degradation experiments; the effect of copper film (CF) as a metal catalyst was also tested. The BPA degradation efficiency of PDS as an oxidizing agent was compared to H2O2 under US irradiation; PDS was effectively activated by ultrasound and through ultrasound-derived heat. The presence of CF in the system was also observed to significantly enhance BPA degradation. The performance of three single systems (US, PDS, and CF), three dual systems (US-PDS, US-CF, and PDS-CF), and one triple system (US-PDS-CF) were compared. It was found that the US-PDS-CF triple system exhibited the highest BPA degradation of 99.51% within 30 min. The effect of operating parameters on degradation efficacy was investigated; BPA degradation was stimulated by the elevation of ultrasound power (38.87–97.17 W), temperature (30–70 °C), and initial PDS concentration (1.71–17.11 mM). Artificial neural network modeling was utilized to determine the significance of these operational parameters in BPA degradation. It was estimated that the importance of these parameters was, in order, temperature (46.83%) > initial PDS concentration (40.54%) > ultrasound power (12.63%). Furthermore, BPA mineralization was studied in the US-PDS and US-PDS-CF systems. These findings facilitate an understanding of the US-PDS process to degrade organic compounds.
Keywords: Artificial neural networks; Bisphenol A; Peroxydisulfate; Temperature; Ultrasound